2020
DOI: 10.3390/su12103967
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Basic Oxygen Furnace Slag in Geopolymeric Coating for Passive Radiative Cooling Application

Abstract: Basic oxygen furnace slag (BOFs) is difficult to reutilize because it contains excessive free lime, and thus causes serious expansion. For this reason, how to reuse BOF slag has turned out to be an imperative issue in order to meet the concept of a circular economy. The key intention of this research work is to develop a new way to reutilize BOF slag, which due to its high emissivity in the 8–13 µm wavelength range, can be used as a sustainable, passive radiative cooling material. Passive radiative cooling, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…From the Frattini test, BOF had 90% lime removal, FA had 47%, and IOT had 30%, indicating high, considerable, and reduced pozzolanic activity, respectively. These results are found to be in correlation with previous findings [59,60], which have reported similar degrees of pozzolanicity for these materials.…”
Section: Frattini Testsupporting
confidence: 93%
“…From the Frattini test, BOF had 90% lime removal, FA had 47%, and IOT had 30%, indicating high, considerable, and reduced pozzolanic activity, respectively. These results are found to be in correlation with previous findings [59,60], which have reported similar degrees of pozzolanicity for these materials.…”
Section: Frattini Testsupporting
confidence: 93%
“…Therefore, it was difficult to make a comparison with the earlier investigations. 6,8,10,18 However, the radiative cooling effect of the Si 2 N 2 O particles added cement composite material was sufficiently observed, and we suggested the composites of this study was a passive cool system for the cement structure by radiative cooling.…”
Section: Resultsmentioning
confidence: 71%
“…The 2 wt.% and 10 wt.% specimens with 10 mm thickness showed significant radiative cooling of 0.92 W/m 2 and 0.56 W/m 2 respectively at 90 • C. Earlier studies investigated the radiative cooling effect between "ambient" and "radiative cooling material". 6,8,10,18 This investigation evaluated the "radiative cooling effect as the material" between a "blank" and a "radiative cooling composite" under ambient temperature. Therefore, it was difficult to make a comparison with the earlier investigations.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that this coating had an obvious radiation cooling effect and great insulation ability owing to the emissivity and reflectivity. Furthermore, the adhesion and weather resistance were maintained at a certain level [16].…”
Section: Introductionmentioning
confidence: 99%